Healthcare Needs of Patients with Amyotrophic Lateral Sclerosis (ALS) in Singapore: A patient-centred qualitative study from multiple perspectives. Issue 3 (September 2015) - Ang, Kexin; Umapathi, Thirugnanam; Tong, Jieli; Ng, Justin; Tseng, Liang Jun; Woo, Ivan Mun Hong
Background: One challenge for those who manage amyotrophic lateral sclerosis (ALS) is to understand patients' needs. Aim: The aim of this study was to examine the needs of Singapore ALS patients from their perspective as well as that of their caregivers and healthcare professionals in order to develop a template for better services. Methods: A cross-sectional qualitative study was conducted, with one-to-one interviews and focus group discussions. Results: All 30 participants, key stakeholders in the field of caring for ALS patients, identified these needs categories: psychological – diagnosis must be staged and comfortably paced, and efforts must be made to encourage patients' resilience; social – positive relationships, open communication, and spiritual support must be developed; physical – attention should be paid to alleviating discomfort and disability; and environmental -appropriate services should be made available. Conclusion: The identified needs categories do overlap, but there are significant differences. Our findings provide a template for developing individualized patient services, which should be done within the framework of a comprehensive palliative care program.